Economic growth and business cycle: The case of Thailand - Paravee Maneejuk (2018)
© Serials Publications Pvt. Ltd. This study is aimed at analyzing business cycle in Thailand using a Markov-switching Vector Autoregressive approach with a special concern about structural changes. Our specific interests are to examine the cyclical movements among economic activities, and to detect the nonlinear economic growth through the context of business cycle. Empirical results show that all parameters are statistically significant and differ across economic stages. These significant results can, in turn, support the aspects of comovement of different economic activities over the business cycle and also the existence of distinct relationships among these variables across different economic regimes. Additionally, the economic growth as measured by growth rate of real GDP, is affected by changes in the economic activities in which magnitude of effects are differ across regimes. This result reasonably supports the persistence of nonlinear economic growth path as being due to the fluctuation in economic activities associated with business cycle.